Aplikasi Teori Humanistik dalam Interaksi Guru-Siswa di Kelas - Herman Nirwana (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
The Application of Humanistic Theory to Teacher-student Classroom Interaction. Humanistic theory emphasizes equal development of students' cognitive and affective aspects. In a humanistic teaching, students have to study and record the progress they have made by themselves. Although the theory has not yet been implemented in our school setting, it can actually be applied in the interaction between the teacher and students in the classroom. The teacher gives the freedom and responsibility to the students to study and functions as a facilitator, who facilitates the students to freely express their feelings and emotions.